The Impact Ground Phonolite Rock’s Potassium Solubilization in Tropical Soil Depends on the Cultivated Forage Species - Alaor Ribeiro da Rocha Neto; Renato de Mello Prado; Mara Cristina Pessôa da Cruz (Plants, 2024)
Cover crops can be used to accelerate the solubilization process of low-solubility fertilizers; thus, the aim of this study was to evaluate the potential of grasses in solubilizing potassium from phonolite rock powder. With a 2 × 5 factorial scheme, two doses of phonolite rock powder, equivalent to 0 and 8 t ha−1, were combined with four grass species (Urochloa ruziziensis, U. decumbens, U. humidicola, and Andropogon gayanus), besides a control treatment without any cover crop. The dry matter production of the aerial parts of the plants was evaluated at days 40 and 70 post-emergence, and then the concentration of potassium in the plants and the soil was evaluated (exchangeable, non-exchangeable, structural, and total potassium contents). In the soil, the phonolitic rock powder increased the exchangeable, non-exchangeable, structural, and total K contents, favoring the absorption of K and the production of the dry mass of the three Urochloa, but U. decumbens stood out because it promoted greater availability of K in the system compared to the cultivation of other plant species. This research proposes the inclusion of U. decumbens in production systems that receive phonolitic rock, constituting a sustainable strategy to improve its agronomic efficiency.